Selective spraying of grapevines for disease control using a modular agricultural robot. (June 2016) - Oberti, Roberto; Marchi, Massimo; Tirelli, Paolo; Calcante, Aldo; Iriti, Marcello; Tona, Emanuele; Hočevar, Marko; Baur, Joerg; Pfaff, Julian; Schütz, Christoph; Ulbrich, Heinz
Abstract : Due to their recognised role in causing environmental pressures, the need to reduce production costs and public concerns over the healthfulness of fresh products and food, reducing pesticide use in agriculture is a major objective. In current farming practice, pesticides are typically applied uniformly across fields, despite many pests and diseases exhibiting uneven spatial distributions and evolving around discrete foci. This is the fundamental rationale for implementing the selective targeting of pesticide applications such that pesticides are deposited only where and when they are needed and at the correct dose. This approach is explored using the example of powdery mildew on grape vines controlled by means of a modular agricultural robot developed within the EU-project CROPS. The CROPS manipulator was configured to six degrees of freedom and equipped with a new precision-spraying end-effector with an integrated disease-sensing system based on R-G-NIR multispectral imaging. The robotic system was tested on four different replicates of grapevine canopy plots (5 m in length × 1.8 m in height) prepared in a greenhouse setup by aligning potted plants exhibiting different levels of disease. The results indicate that the robot was able to automatically detect and spray from 85% to 100% of the diseased area within the canopy and to reduce the pesticide use from 65% to 85% when compared to a conventional homogeneous spraying of the canopy. This work, to the best of our knowledge, is the first using a totally automatic selective system for spraying of diseases in specialty crops. Highlights: A totally automatic selective spraying system for diseases in specialty crops. A modular agricultural robot was configured for precision-spraying applications. Multispectral imaging disease detection system integrated with manipulator control. Selective spraying experiments conducted on powdery mildew disease in grapevine. Pesticide use significantly reduced compared to conventional homogeneous spraying.